Prevalence of malnutrition and associated risk factors among adult visceral leishmaniasis patients in Northwest Ethiopia: a cross sectional study - Mengesha, Bewketu (BioMed Central, 2014)
BACKGROUND: Visceral leishmaniasis (VL) causes considerable morbidity and mortality in Ethiopia. Data on the prevalence and associated risk factors on malnutrition among VL patients in Ethiopia are scarce. This study aimed to assess the prevalence of malnutrition and its associated risk factor among VL patients in Northwest Ethiopia. METHODS: An institution-based cross-sectional study was conducted from June to September 2012 at four leishmaniasis treatment sites in Northwest Ethiopia. Four hundred and three adult VL patients were enrolled in the study. Malnutrition was defined as a body mass index (BMI) ≤ 18.5 kg/m2. The data collected from the VL patients included sex, age, residence, occupation, weight, height, laboratory results (HIV, hemoglobin, intestinal parasites). Multivariate logistic regression model was used to determine the strength of association between malnutrition and associated risk factors. RESULTS: Among 403 adult VL patients 385 (95.5%) were malnourished. Twenty eight percent (n = 113), 30.3% (n = 122), and 37.2% (n = 150) were mildly, moderately and severely malnourished, respectively. The prevalence of intestinal parasitic infection was 47.6% (n = 192) and it was associated with malnutrition (P = 0.01). The prevalence of VL-HIV co-infection was 10.4% (n = 42). Hook worm, Giardia intestinalis and Ascaris lumbircoides were the leading prevalent intestinal parasites. Factors such as age, sex, residence, occupation, HIV status and anemia were not associated with severe malnutrition. CONCLUSIONS: The prevalence of malnutrition in VL patients was very high and it was associated with intestinal parasitic infections. Therefore, screening of severely malnourished VL patients for intestinal parasitic infections during admission is recommended.